Dendrobium Orchid Decorative Plant Business - Siti Rochaeni; Prasetyo Nugroho; Armaeni Dwi Humaerah; Achmad Tjahja Nugraha (JURNAL AGRIBISNIS TERPADU, 2023)
Horticultural crop, especially orchids, have quite high economic value with good business prospects. Nevertheless, the sales of orchid in Kebun Anggrek Nugroho (Nugroho’s Orchid Farm) experienced some fluctuation and tend to drop during COVID-19 pandemic. This condition has impact on business revenue, which will then affect the sustainability. The objectives of this research are: (1) Analyse cost structure of orchid plant growing business; (2) Analyse the income; (3) Analyse the business according to financial criteria. The data source is both primary (observation and interviews) and secondary (literature review). Microsoft Office Excel was used for processing quantitative data. Analytical method that was being used were business cost structure analysis, revenue and income analysis, B/C ratio, Break Even Point (BEP), and Payback Period (PP). The result showed that: (1) Kebun Anggrek Nugroho spent more on variable cost than fixed cost with 97,38% to 2,62% ratio; (2) The operating income earned is IDR 241.873.190 per production period; (3) The B/C ratio obtained is 1,16 which means the business is profitable. The production volume and selling price are greater than BEP value, also indicated that the business is profitable. The PP value is 0,31 meant that a return on capital will be gained within 3 months 22 days.